Dvije Pertle Pod Istim Krovor - Begović, Nedžad (Bosnia and Hercegovina, 2013)
A love story featuring a married couple with differing political views.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films